Preserving Celery Quality: Organic Cultivation and Room Temperature Storage with LDPE Wrapping Yields Optimal Results - Jannah Z; Saidi I A; Sutarman; Holmurodovich M A (BIO Web of Conferences, 2023)
Periodic use of chemical pesticides in conventional farming systems can lead to environmental degradation. Organic product are believed to be potential for human health. This research was conducted for 144 hours to determine the effect of cultivation and storage methods on the chemical-physical, and organoleptic characteristics of celery during the post-harvest period. This study used a Factorial Randomized Block Design which was repeated three times with the first factor is the cultivation method which consisted of two levels, namely, organic and conventional. The second factor was the storage method which consisted of four levels, namely, stored in the refrigerator with wrapped in LDPE Bag, stored in the refrigerator without wrapping in LDPE Bag, stored in a room temperature wrapping in LDPE bag, and stored in a room temperature without wrapping in LDPE bag. Data obtained were analysed by analysis of variance and then continued with the 5% HSD Test. The results of weight loss showed that the best treatment was obtained in organic cultivation with the scores 48.03% and stored in the room temperature with LDPE bags with the scores 18,31%, and the organoleptic scores were colour 4.13, and freshness value 4.17.